2017
DOI: 10.3892/or.2017.6121
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the SPARC promoter and its prognostic value for prostate cancer

Abstract: Secreted protein acidic and rich in cysteine (SPARC) is a secreted matricellular glycoprotein and plays a key role in the development of many tissues and organ types. However, the role of SPARC in prostate cancer (PCa) is still controversial. The aim of the present study was to investigate the abnormalities in the expression of SPARC and its promoter hypermethylation in prostate cancers and in correlated clinicopathological profiles. We examined the hypermethylation of the SPARC promoter as a potential mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Therefore, we believe that SPARC might play a role as a tumor suppressor gene in GC. SPARC has also been found to be downregulated in some other types of cancer, including neuroblastoma[16], ovarian cancer[17], pancreatic cancer[8], colon cancer[9], bladder cancer[18], prostate cancer[19], and acute leukemia[20]. When analyzing these tumors genetically, it is common to find that the promoter region of the SPARC gene in these tumors was in a state of abnormal hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that SPARC might play a role as a tumor suppressor gene in GC. SPARC has also been found to be downregulated in some other types of cancer, including neuroblastoma[16], ovarian cancer[17], pancreatic cancer[8], colon cancer[9], bladder cancer[18], prostate cancer[19], and acute leukemia[20]. When analyzing these tumors genetically, it is common to find that the promoter region of the SPARC gene in these tumors was in a state of abnormal hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…24 SPARC expression was decreased in PCa cell lines because of hypermethylation of the SPARC promoter, and SPARC hypermethylation was correlated with a poorer prognosis in PCa patients. 25 In colorectal cancer (CRC), high stromal SPARC indicated poor prognosis in CRC patients, and fibroblast-derived SPARC enhanced tumor cell invasion; 26 however, other studies revealed that low expression of SPARC in CRC tissue is associated with poor prognosis and aggressive clinicopathological features. 27,28 In studying the relationship between SPARC and gynecological tumors, we also found contradictory results.…”
mentioning
confidence: 99%
“…Second, wet experiments (IHC, qRT-PCR, overexpression, or knockdown) should be performed to elucidate the expression and roles of the signature genes in PCa because most of them were not reported previously and some were even contradictory. Third, the coexpression relationship between lncRNAs and mRNAs should be explored by chromatin immunoprecipitation, RNA immunoprecipitation, and biotin-labeled RNA pull-down assays [ 49 ].…”
Section: Discussionmentioning
confidence: 99%